2017
DOI: 10.1088/1742-6596/847/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

EPID-based dosimetry and its relation to other 2D and 3D dose measurement techniques in radiation therapy

Abstract: The three-dimensional scintillation dosimetry method: test for a 106Ru eye plaque applicator A S Kirov, J Z Piao, N K Mathur et al. Abstract. In this paper I will summarize the possibilities and limitations of different 2D and 3D dosimetry techniques used in radiation therapy, and evaluate these features relative to those of EPID-based techniques. After briefly discussing their characteristics, I will review the use of EPIDs for pre-treatment and in vivo dosimetry applications by separating them into transit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…48 Electronic portal imaging devices (EPIDs) are not suitable for PSQA with couch rotations since the TPS dose object is tied to the rotating couch while the EPID remains stationary with respect to the gantry. Additionally, EPIDs over-respond to low-energy photons, 49 and have a dose rate dependence. 50 Studies with EPIDs have shown 16-23% errors in output factors for small field size (~8 mm 2 x 8 mm 2 ) in one study 51 and ~8% difference to film for measurements of small target plans (~3 mm 2 x 3 mm 2 ) in another.…”
Section: Introductionmentioning
confidence: 99%
“…48 Electronic portal imaging devices (EPIDs) are not suitable for PSQA with couch rotations since the TPS dose object is tied to the rotating couch while the EPID remains stationary with respect to the gantry. Additionally, EPIDs over-respond to low-energy photons, 49 and have a dose rate dependence. 50 Studies with EPIDs have shown 16-23% errors in output factors for small field size (~8 mm 2 x 8 mm 2 ) in one study 51 and ~8% difference to film for measurements of small target plans (~3 mm 2 x 3 mm 2 ) in another.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, electronic portal imaging devices (EPIDs), previously used for pretreatment checks in radiotherapy, have gained popularity for in vivo verification measurements 1,2 . Electronic portal imaging device transmission measurements have shown utility in detecting patient‐related errors and also have been used clinically to identify meaningful errors that would otherwise go undetected by standard pretreatment quality assurance (QA) checks 3–5 . However, given the recent utilization of EPID images for in vivo treatment QA, there is currently no consensus regarding the ability of EPID images to detect deviations during treatment that could impact the intended dose distribution.…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition to the various modes of acquisition, the delivered dose can be estimated using several different approaches, including predicted forward-projected EPID comparisons and simple back-projection of measured data. 6,[8][9][10] It is becoming increasingly popular to use transmission EPID-based dosimetry to verify that the patient's received dose is correct and multiple commercial systems are now available for use. 6,8,11,12 One such approach is to use the 3D reconstructed EPID dose to calculate dose-volume histogram (DVH) statistics in the planning computed tomography (pCT) dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Although these are useful metrics to quantify the repeatability of treatment fractions, these methods do not provide DVH-specific statistics that relate the delivered dose to the planning target volume (PTV). 6,8,9,[12][13][14] To address this issue, a new analysis technique was introduced as a pre-treatment verification method in a doctoral dissertation that did not require recalculation of EPID-based data to patient dose, or analysis by means of the pass/fail gamma criteria. 15 Recently, Steers et al 16 published their work on applying the gradient dose segmented analysis (GDSA) technique to in-vivo EPID images for dose verification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation